Intellectual capital-enhancing HR, absorptive capacity and innovation - Soo, C.; Tian, Amy; Teo, S.; Cordery, J. (Wiley, 2016)
This study investigates the role of intellectual capital (i.e., human, social, and organization capital)–enhancing human resource (HR) practices in the development of a firm's absorptive capacity, as well as the mediating role of absorptive capacity in its relationship to the firm's innovation performance. Results show that while human capital–enhancing HR (acquisition and developmental HR) is positively related to absorptive capacity, social capital–enhancing HR affects absorptive capacity through egalitarian HR practices. Organization capital–enhancing HR practices contribute to absorptive capacity through effective information systems. Finally, our findings confirm that the various intellectual capital–enhancing HR practices affect innovation performance through their impact on the firm's absorptive capacity.